1999
DOI: 10.1177/105268469900900301
|View full text |Cite
|
Sign up to set email alerts
|

Five Faces of Trust: An Empirical Confirmation in Urban Elementary Schools

Abstract: After an extensive review of the literature on trust, a multi-faceted definition of faculty trust was developed at three organizational levels: trust in principal, trust in colleagues, and trust in clients. Along with a general willingness to risk vulnerability, five faces of trust emerged: benevolence, reliability, competence, honesty, and openness. This conceptual formulation of faculty trust was then subjected to empirical test, which supported the theoretical underpinnings of the construct. Finally, three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
361
0
23

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(399 citation statements)
references
References 23 publications
(15 reference statements)
15
361
0
23
Order By: Relevance
“…Throughout the 1980s and 1990s, organizational theorists and institutional researchers, have pursued the concept of trust and how it is cultivated and utilized in organizational settings. Research has also indicated that trust represents a critical element in the development of healthy and purposefully directed school environments (Hoy et al 1996;1992;Hoy and Tschannen-Moran 1999;Smith and Birney 2005;Smith et al 2001;Tarter et al 1989a;. Moreover, studies of trust and climate reveal that certain administrator behaviors Hoy and Henderson 1983;Hoy and Kupersmith 1985) and collegial interactions (Hoy et al 1992;Tarter et al 1989aTarter et al , b, 1995 do indeed buttress the case that trust is critical in healthy and open learning environments.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Throughout the 1980s and 1990s, organizational theorists and institutional researchers, have pursued the concept of trust and how it is cultivated and utilized in organizational settings. Research has also indicated that trust represents a critical element in the development of healthy and purposefully directed school environments (Hoy et al 1996;1992;Hoy and Tschannen-Moran 1999;Smith and Birney 2005;Smith et al 2001;Tarter et al 1989a;. Moreover, studies of trust and climate reveal that certain administrator behaviors Hoy and Henderson 1983;Hoy and Kupersmith 1985) and collegial interactions (Hoy et al 1992;Tarter et al 1989aTarter et al , b, 1995 do indeed buttress the case that trust is critical in healthy and open learning environments.…”
mentioning
confidence: 85%
“…Researchers and scholars consistently recognize honesty as a salient aspect of trust (Butler and Cantrell 1984;Cummings and Bromily 1996;Hoy and Tschannen-Moran 1999). Honesty conveys straightforwardness of conduct, integrity, and probity to persons in a relationship.…”
Section: Honestymentioning
confidence: 97%
See 1 more Smart Citation
“…When teachers make trust discernments based on their own willingness to be vulnerable to another role group, they interpret the other parties' actions in terms of benevolence, reliability, competence, openness, and honesty (Hoy and Tschannen-Moran 1999). Trust also takes different forms at different stages of a relationship (Tschannen-Moran and Hoy 2000).…”
Section: Teacher Trust In Schoolsmentioning
confidence: 99%
“…To our knowledge, this study is the first to associate the organizational school context with a quantitative measure of individual teacher trust in students across a representative sample of secondary schools (in Flanders, the Dutch-speaking region of Belgium). Whereas Bryk and Schneider (2002) acknowledge the importance of studentteacher trust relations, they do not measure teacher trust in students empirically, and where Hoy and others do measure it, they measure 'faculty trust', that is the degree of collective trust of a school's faculty, based on teachers' perceptions about the nature of their colleagues' trust in students (see for example Hoy and Tschannen-Moran 1999;Forsyth 2008;Van Maele and Van Houtte 2009). Our trust-items, although derived from the Hoy and Tschannen-Moran trust-scale (1999), make no reference to the teaching colleagues in school, resulting in a measure for individual teacher trust in students (see Measures section).…”
mentioning
confidence: 96%